Clinical and pathologic features of out-of-hospital cardiac arrest in pregnancy: insights from a state-wide registry. (3rd October 2022) - Paratz, E; Rowe, S; Van Heusden, A; Thompson, T; Morgan, N; Smith, K; James, P; Pflaumer, A; Connell, V; Semsarian, C; Ingles, J; Parsons, S; et al.
Abstract: Background: Cardiovascular disease is the most common cause of indirect maternal mortality worldwide, and cardiac arrest occurs in up to 1 in 12, 000 pregnancies. Objective: To define rates, clinical and pathologic factors of out-of-hospital cardiac arrest (OHCA) in pregnant and post-partum females. Methods: A prospective state-wide cardiac arrest registry combining ambulance, hospital and forensic data captured all OHCAs from 2019–2021. Clinical and pathological details for pregnant patients were identified. Results: 1, 482 OHCAs occurred, including 376 females of child-bearing age of whom eight were pregnant or post-partum. OHCA incidence was lower in pregnant females compared to non-pregnant females of child-bearing age (5.2 OHCAs per 100, 000 pregnant females vs 23.1 per 100, 000 females of child-bearing age, p<0.0001). Seven patients (87.5%) died, with five (62.5%) having a cardiac cause of OHCA (unascertained = 2, cardiomyopathy = 2 (1 hypertrophic), ischemic heart disease = 1). Two patients had pre-existing cardiac risk factors, but none had a cardiac diagnosis pre-arrest. Compared to in-hospital cardiac arrests (IHCAs) in pregnancy, OHCAs are more likely to have a cardiac cause (odds ratio 3.81) and lower maternal survival (odds ratio 0.09). Conclusion: Maternal OHCA affects approximately 1 in 20, 000 pregnancies with high maternal mortality rates. OHCA occurs at one-quarter the rate in non-pregnant females of child-bearing age. Approximately two-thirds of maternal OHCAs had an underlying cardiac cause, but low rates of cardiac diagnosis pre-arrest. OHCAs differ markedly from IHCAs in pregnant females, requiring ongoing evaluation as to specific causes and preventability. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): NHMRC, NHF